Age Related Optimal Income Taxation - Sören Blomquist; Luca Micheletto (Uppsala University, Department of Economics, 2003)
The focus of the present paper is on the intragenerational effects of nonlinear income taxation in a multiperiod framework. We investigate whether it is possible to achieve redistribution at smaller efficiency costs by enlarging the message space adopted in standard tax system (which only includes reported income) to consider also the age of taxpayers. Since it would be awkward to analyze an age related tax without taking into account the time-dimension, we use an intertemporal extension of the Stiglitz-Stern (1982, 1982) discrete adaptation of the Mirrlees (1971) optimal income taxation model. In the simplest version of the model we neglect the possibility of savings. This case can be interpreted as a situation with extreme liquidity constraints. It is shown that switching to an age related tax system opens the way for a Pareto improving tax reform entailing a cut in marginal tax rates for young agents. In a second version of the model we retain the possibility of savings and, assuming that the policy maker can tax interest incomes on a linear scale, we also analyze the optimal values of the interest income tax rate for the age dependent and the age independent tax systems.
urn:nbn:se:uu:diva-4461
Keywords: H21; H23; H24; 330; Optimal taxation; age specific taxes; tagging; Optimale Besteuerung; Altersgruppe; Theorie